Human Rights at the Intersections Transformation through Local, Global, and Cosmopolitan Challenges - Chase, Anthony Tirado; Mahdavi, Pardis; Banai, Hussein; Gruskin, Sofia (Bloomsbury Academic, 2022)
At a time when states are increasingly hostile to the international rights regime, human rights activists have turned to non-state and sub-state actors to begin the implementation of human rights law. This complicates the conventional analysis of relationships between local actors, global norms, and cosmopolitanism. The contributions in this open access collection examine the "lived realities of human rights" and critically engage with debates on gender, sexuality, localism and cosmopolitanism, weaving insights from multiple disciplines into a broader call for interdisciplinary scholarship informed by practice. Overall, the contributors argue that the power of human rights depends on their ability to be continuously broadened and re-imagined in locales around the world. It is only on this basis that human rights can remain relevant and be effectively used to push local, national and international institutions to put in place structural reforms that advance equity and pluralism in these perilous times. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.